A flow cytometric assay for HLA‐DR expression on monocytes validated as a biomarker for enrollment in sepsis clinical trials. Issue 1 (12th January 2021) - Quadrini, Karen J.; Patti‐Diaz, Lisa; Maghsoudlou, Jasmin; Cuomo, Joanne; Hedrick, Michael Nathan; McCloskey, Thomas W.
Abstract: Purpose: Decreased expression of HLA‐DR on monocytes (mHLA‐DR) is a reliable indicator of immunosuppression in patients with sepsis and is correlated with increased risk of secondary infection and mortality. A flow cytometry‐based laboratory developed test for the measurement of mHLA‐DR in whole blood was validated for clinical trial enrollment, which is considered medical decision‐making, for patients with severe sepsis or septic shock. Methods: The BD Quantibrite™ anti‐HLA‐DR/anti‐monocyte reagent measures antibodies bound per cell of HLA‐DR on CD14+ monocytes. The mHLA‐DR assay was planned to support inclusion/exclusion of patients for a clinical trial and was validated according to New York State Department of Health (NYSDOH) requirements for a new non‐malignant leukocyte immunophenotyping assay. Results: Normal, healthy donor and sepsis patient samples were stable up to 72 h post‐collection in Cyto‐Chex BCT phlebotomy tubes. Pre‐determined acceptance criteria were met for precision parameters (average %CV ≤ 20%) and global laboratory‐to‐laboratory comparisons (average %Δ ≤ 20%). The approaches taken to evaluate and report accuracy, analytical specificity and sensitivity, reportable range, reference interval, and the proposed multi‐level quality control were accepted by NYSDOH. Conclusions: In this study, the validation strategy necessary when the intended use of assay results changes from exploratory to medical decision making (patient enrollment), which successfully resulted in regulatory approval, is described.